Géographies de la nuit / Geographies of the night / Geografie della notte - Luc Gwiazdzinski; Marco Maggioli; Will Straw (Bollettino della Società Geografica Italiana, 2019)
Geographies of the night. This intervention invites us to explore “geographies of the night” at multiple levels, in different contexts and through different approaches. If this project seeks to map out the geographies of a particular astronomical moment in the 24-hour cycle, it also aims to reflect on the emergence of a specific branch of the discipline, one with its own concepts, methods and tools. This is both a reflection “on” the night, “with” and “through” geography and an interrogation of geography from the perspective of night. In this article, we will begin by tracing the pressures which act upon the night and have made it a present-day concern, a preoccupation of public policy and an object of research in geography and across the social sciences and humanities. In a second movement, we will analyse research on the night within the discipline and trace the emergence of an interdisciplinary field of research: “night studies”. Finally, we will explore the possible contributions of a “night” turn for geography. From such a perspective, the night is simultaneously a matter, an infrastructure, an object, an environment, an ambiance and a generator of research.